Employees' collective rights in the public sector : general and national reports : XIVe Congrès international de droit comparé = XIVth International Congress of Comparative Law, Athens, August 1994 /: general and national reports : XIVe Congrès international de droit comparé = XIVth International Congress of Comparative Law, Athens, August 1994. (1997) - Unknown
No abstract available